2014
DOI: 10.1590/0001-3765201420130048
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic, antifungal, trypanocidal and leishmanicidal activities of acetogenins isolated from Annona cornifolia A. St. -Hil. (Annonaceae)

Abstract: Annona cornifolia A. St. -Hil. is a small annual perennial tree found in the Brazilian savannah; their green fruit is popularly used in the treatment of ulcers. The acetogenins isolated from the seeds of Annona cornifolia previously showed to possess antioxidant activity. In continuation of our investigations on the biological activities of acetogenins, four binary mixtures and ten pure adjacent bis-tetrahydrofuran annonaceous acetogenins were evaluated: the cytotoxic (against three human tumor cell lines), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The present study demonstrated the antifungal activity of liriodenine against three fungal strains of the genus Paracoccidioides ; however, greater activity was observed against yeasts of the genus Cryptococcus and against the thermally dimorphic fungus Histoplasma capsulatum . Among the studies focusing on the genus Paracoccidioides , two extracts derived from the genus Annona [ 46 , 47 ] and three evaluated compounds extracted from other plant species [ 48 - 50 ] were used. In this respect, Lima et al [ 46 ] evaluated the activity of fatty acid methyl esters (FAMEs) against 12 clinical isolates of P. brasiliensis by the broth microdilution method and observed inhibition of all isolates, with MIC values ranging from 3.4 to 55.5 μg.mL -1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated the antifungal activity of liriodenine against three fungal strains of the genus Paracoccidioides ; however, greater activity was observed against yeasts of the genus Cryptococcus and against the thermally dimorphic fungus Histoplasma capsulatum . Among the studies focusing on the genus Paracoccidioides , two extracts derived from the genus Annona [ 46 , 47 ] and three evaluated compounds extracted from other plant species [ 48 - 50 ] were used. In this respect, Lima et al [ 46 ] evaluated the activity of fatty acid methyl esters (FAMEs) against 12 clinical isolates of P. brasiliensis by the broth microdilution method and observed inhibition of all isolates, with MIC values ranging from 3.4 to 55.5 μg.mL -1 .…”
Section: Discussionmentioning
confidence: 99%
“…This MIC range was similar to that observed in the present study. In another study, Lima et al [ 47 ] investigated the activity of acetogenins extracted from Annona cornifolia against Pb01 and Pb18 by the broth microdilution method. Concentrations of 1.17 to 150 μg.mL -1 were tested.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of annonacin has also been demonstrated against bladder cancer (T24), breast cancer (MCH7) and skin cancer (BCC-1) with IC 50 s 0.324, 0.433 and 0.427 µg/mL, respectively [ 172 ]. The cytotoxicity of five other acetogenins (squamocin M, annofolin, isolongimicin B, glaucanisin, and annotacin) isolated from A. cornifolia against human breast cancer (MCF-7) was reported, with IC 50 s of approximately 0.3 µM [ 173 ]. In an in vitro study, the annoaceous acetogenins laherradurin and cherimolin-2 isolated from A. diversifolia were shown to have ED 50 s of 0.015 and 0.05 µg/mL, respectively, against the cervical cancer cell line (HeLa) [ 174 ].…”
Section: Pharmacological Properties Of Annona Speciesmentioning
confidence: 99%
“…Medicinal plants are defined as those capable of producing active ingredients that treat several diseases and hence achieving an important role in global health (Lima et al, 2014). Studies show that, in Brazil, about 91% of the population makes use of some medicinal plants, and 46% of them keep these plants homegrown (Ethur et al, 2011).…”
Section: Introductionmentioning
confidence: 99%